'A not unedifying field for some local antiquary of the future': new evidence on library activity and mutual improvement. The experience of the north-east of Scotland. (April 2020) - Crawford, John C.
Abstract : Mutual improvement, an early form of lifelong learning, was widespread among the nineteenth-century working classes and has been portrayed as a variable and relatively unstructured phenomenon. This essay challenges this view by examining the movement in north-east Scotland in the nineteenth century and its symbiotic relationship with library activity as libraries provided information to facilitate debate. The movement originated in the 1830s and flourished until the end of the century. Mutual improvement activity was fuelled by religious division and a relationship with the Liberal Party. The principal ideologue of the movement, which peaked in the 1850s, was Robert Harvie Smith, who articulated a sophisticated lifelong learning ideology supported by specific learning objectives, prioritised in order. A notable feature was the involvement of women in the movement. Most of the participants were tradesmen or small tenant farmers, and the subjects of their debates reflected their preoccupations: modern farming, religious controversy, and the 'farm servant problem'. The movement anticipated the university extension movement by about thirty years. Because the north-east had its own university and was a self-contained learning culture, mutual improvers might proceed to university, thus anticipating modern ideas about received prior learning (RPL) and articulation. Mutual improvement activity demonstrates the continuing intellectual vitality in rural Scotland in the late nineteenth century.